2014
DOI: 10.1007/s11356-014-2979-4
|View full text |Cite
|
Sign up to set email alerts
|

Overview on the European green crab Carcinus spp. (Portunidae, Decapoda), one of the most famous marine invaders and ecotoxicological models

Abstract: Green crabs (Carcinus, Portunidae) include two species native to Europe--Carcinus aestuarii (Mediterranean species) and Carcinus maenas (Atlantic species). These small shore crabs (maximal length carapace, approximately 10 cm) show rapid growth, high fecundity, and long planktonic larval stages that facilitate broad dispersion. Carcinus spp. have a high tolerance to fluctuations of environmental factors including oxygen, salinity, temperature, xenobiotic compounds, and others. Shipping of Carcinus spp. over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 205 publications
0
67
0
Order By: Relevance
“…In contrast to the pattern for temperature, larvae are less tolerant of salinity fluctuations than juveniles but juveniles are still more tolerant than adults [12,117,118,120,123,124]. Anger et al [125] found that C. maenas early larvae from the North Sea showed reduced respiration at low salinities, suggesting a very low or lacking osmoregulatory capacity, but salinity tolerance increases with successive larval stages to megalopae and euryhalinity is finally achieved in juveniles [114,126].…”
Section: Salinitymentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to the pattern for temperature, larvae are less tolerant of salinity fluctuations than juveniles but juveniles are still more tolerant than adults [12,117,118,120,123,124]. Anger et al [125] found that C. maenas early larvae from the North Sea showed reduced respiration at low salinities, suggesting a very low or lacking osmoregulatory capacity, but salinity tolerance increases with successive larval stages to megalopae and euryhalinity is finally achieved in juveniles [114,126].…”
Section: Salinitymentioning
confidence: 99%
“…Larvae exhibit higher physiological tolerance to temperature fluctuations than adults [112,113] and juveniles are more tolerant of temperature variations than older individuals [12,120,124]. deRivera et al [113] found that mortality of cultured larvae at temperatures below 12.5°C was very high due to extended exposure to cold.…”
Section: Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Consequently, it has been used to assess the impact of metals, 3 pesticides, 4 xenostrogens 5 and drugs. 6 Naturally, shore crabs display a high tolerance to fluctuations of abiotic factors in their environment, which may entail hypoxia, salinity changes or temperature stress (heat-shock and/or cold shock, respectively).…”
Section: Introductionmentioning
confidence: 99%